Other slides in this set

Slide 2

Preview of page 2

Here's a taster:

First of all, I would like to ask you to
take your time with this. Really
think about each step and think
about how/why it works. If you
have any topics that you want
covered then please contact me at
Username: David…read more

Slide 3

Preview of page 3

Here's a taster:

Step 1
· If y = 3x ­ 1 then what is y² ?
· y² = (3x-1)²
· So... put it in the y² equation:
· x² + (3x-1)² = 40…read more

Slide 4

Preview of page 4

Here's a taster:

Step 2
· Expand the brackets:
· (3x-1)²= (3x-1)(3x-1)
· 3x*3x=9x²
· 3x*-1=-3x
· 3x*-1=-3x
· -1*-1=1
· So: 9x²-3x-3x+1 simplifies into
· 9x²-6x+1…read more

Slide 5

Preview of page 5

Here's a taster:

Step 3
· Now we have our original equation but
instead of y² we have 9x²-6x+1:
· x²+9x²-6x+1=40
· Yes, we can simplify this into:
· 10x²-6x=39…read more

Slide 6

Preview of page 6

Here's a taster:

Step 4
· Now, we want to make it so that the equation = 0
so we can either factorise it or insert it into the
quadratic equation. This means:
· 10x²-6x-39=0
· We can not factorise this (or it would be VERY
hard) so we will have to use the quadratic equation…read more

Slide 7

Preview of page 7
Preview of page 7

Slide 8

Preview of page 8
Preview of page 8

Slide 9

Preview of page 9
Preview of page 9

Slide 10

Preview of page 10
Preview of page 10


No comments have yet been made

Similar Mathematics resources:

See all Mathematics resources »See all resources »